In Quest of Low‐Leakage Dynamic Random Access Memory Enabled by Doped TiO2 Dielectrics. Issue 2 (4th December 2022) - Ye, Fan; Xue, Kan‐Hao; Yu, Heng; Yang, Shengxin; Yuan, Jun‐Hui; Gu, Rongchuan; Xu, Ming; Miao, Xiangshui
Abstract: High permittivity rutile TiO2 has been regarded as a promising candidate for the capacitor dielectric in ultra‐scaled dynamic random access memory (DRAM), but its low band gap and low interfacial Schottky barrier cause the bothering leakage current problem. It is in principle possible to tune the electrode Fermi level to the mid‐gap of TiO2 for leakage current reduction. In this work, the generalized gradient approximation (GGA)‐1/2 method is shown as a viable first‐principles approach to predict the Schottky barriers of TiO2 based capacitors. Through RuO2 /TiO2 /RuO2 and IrO2 /TiO2 /IrO2 full capacitor calculations, the impact of trivalent cation dopants (Al, Ga, La, and Y) on the Schottky barrier tuning is systematically studied. Among the four dopants, it is discovered that Y doping is most effective in hindering the formation of oxygen vacancies by analyzing formation energy and crystal orbital Hamilton population. Y‐doped rutile TiO2 is a promising material for next‐generation high capacitance and low leakage DRAM capacitors. Abstract : By means of RuO2 /TiO2 /RuO2 and IrO2 /TiO2 /IrO2 DRAM full capacitor calculations, this work systematically studies the impact of trivalent cation dopants (Al, Ga, La, and Y) on the Schottky barrier tuning as well as the leakage current. The ultra‐large supercells (more than 600 atoms) are handled accurately and efficiently in electronic structure calculations with the DFT‐1/2 technique.